Corporate Social Reporting and Stakeholder Accountability: A Case of A Leading It Firm - Anjana Paranamanna; Kalani Dissanayake (International Business and Accounting Research Journal, 2021)
Corporate social reporting is a process of communicating the social and environmental effect of an organization to the particular groups within society and society at large. The Particular groups in the sense consist of individuals, groups or organizations that have a significant interest or concern over the corporation. Accordingly, this study aims to examine the corporate social responsibility practices of a selected company and attempt to reveal how the concept of corporate social reporting affects stakeholder accountability. Qualitative methodology is adopted in this study. Both primary and secondary data were gathered. The primary data were collected through semi-structured interviews and questionnaires. Various documents were used as secondary data sources. Through this study researcher has intensely concentrated on exploring the concept of CSR, its practice and disclosure in a leading Sri Lankan IT company and the study summarized from the review findings that CSR reporting is crucial for discharging accountability to stakeholders. The Study will provide businesses and managers the useful insights for implementing such practices or to further develop corporate social reporting practices as in Sri Lankan context rich CSR initiatives are rarely observable.